Physical Aspects of Healthy Aging: Assessments of Three Measures of Balance for Studies in Middle-Aged and Older Adults. (9th January 2011) - Ceria-Ulep, Clementina D.; Grove, John; Chen, Randi; Masaki, Kamal H.; Rodriguez, Beatriz L.; Donlon, Tim A.; Guralnik, Jack; Willcox, Bradley J.; Willcox, D. Craig; Nigg, Claudio; Curb, J. David
Abstract : Objectives . To investigate the reliability and correlations with age of the balance components of the EPESE, NHANES, and the Good Balance Platform System (GBPS) in a normal population of adults. Design . Cross-sectional. Setting . Urban Medical Center in the Pacific. Participants . A random sample of 203 healthy offspring of Honolulu Heart Program participants, ages 38–71. Measurements . Subjects were examined twice at visits one week apart using the balance components of the EPESE, NHANES, and the good balance system tests. Results . The EPESE and NHANES batteries of tests were not sufficiently challenging to allow successful discrimination among subjects in good health, even older subjects. The GBPS allowed objective quantitative measurements, but the test-retest correlations generally were not high. The GBPS variables correlated with age only when subjects stood on a foam pad; they also were correlated with anthropometric variables. Conclusion . Both EPESE and NHANES balance tests were too easy for healthy subjects. The GBPS had generally low reliability coefficients except for the most difficult testing condition (foam pad, eyes closed). Both height and body fat were associated with GBPS scores, necessitating adjusting for these variables if using balance as a predictor of future health.